(untitled) (Research, Society and Development, 2021)
The production of cassava and tapioca flour are recognized as activities merged in family culture in the North and Northeast regions of Brazil, which demand the use of firewood to feed the furnaces in the flour mills. Due to the small number of studies on this theme, this work aims to evaluate the quality of woody species commonly used as solid fuels in the production of manioc flour in the state of Sergipe, namely: Poincianella pyramidalis (“catingueira”), Cronton sonderianus (“marmeleiro”) and Piptadenia stipulacea (white “jurema”), as well as coconut shells (Cocos nucifera), as an alternative to the use of woody species. Representative samples of the materials were analyzed for parameters: total extracts, lignin, holocellulose, volatile materials, fixed carbon, ashes, higher (HHV) and lower (LHV) heating values, in addition to thermogravimetric analysis. The data were analyzed in a completely randomized design, with four treatments and three replications. The species Piptadenia stipulacea and Cocos nucifera showed high contents of total extracts (18.14%; 29.81%), lignin (29.14%; 28.18%) and fixed carbon (28.22%; 29.62%), and lower contents of holocellulose (52.72%; 42.01%) and volatile materials (70.60%; 66.14%), respectively. The species with the lowest ash content were Croton sonderianus and Piptadenia stipulacea, and the species with the highest HHV and LHV were Piptadenia stipulacea and Croton sonderianus, respectively. Regarding to the thermogravimetric properties, Cocos nucifera behaved like the other biomasses, with ignition temperature slightly lower and peak temperature higher than those for the other species. Among the species analyzed, Piptadenia stipulacea and Cocos nucifera showed the best results as combustibles for cassava flour production. Hence, dried Cocos nucifera shells can properly replace the conventional firewood.